تطوير عملية إدارة النفايات الصلبة البلدية في مدينة اللاذقية باستخدام نظام System Dynamics - شاهين, هيثم; شيبان, سامية (Latakia University Journal -Engineering Sciences Series, 2018)
تواجه اللاذقية الآن الحاجة إلى تحديث نظام إدارة النفايات الصلبة البلدية وذلك وفقاً للزيادة الهائلة في إنتاج النفايات مع تزايد عدد سكان المدينة المفاجئ نتيجة حالة الإيواء بسبب الأزمة.في هذه الدراسة استخدم النموذج الديناميكي الحاسوبي System Dynamics (SD) كمنهجية لتحليل نظام إدارة النفايات الصلبة البلدية الحالي, ولتطوير الاستراتيجية المستقبلية الأمثل. تم بناء النموذج بعد المقارنة بين سيناريو يأخذ بعين الاعتبار العاملين الأكثر تأثيراُ بتوليد النفايات وهما عدد السكان، والعامل الاقتصادي الذي يعبر عنه بالناتج الإجمالي المحلي كمؤشر لمستوى المعيشة وسيناريو أخر لا يأخذ العامل الاقتصادي المتراجع في ظل الأزمة (تنبأ بكمية نفايات 400 ألف طن/سنة للعام 2025) وتم اعتماد هذا السيناريو الأخير في النموذج بوصفه الأخطر. بناءً على نتائج النموذج الديناميكي من المتوقع انخفاض معدل إنتاج الفرد من النفايات من 1.1 قبل الأزمة إلى 0.8 كغ/للشخص .اليوم خلالها وزيادة في عدد السكان ليصبح 1452000 نسمة عام 2025. أظهر النموذج عجزاً في ميزانية إدارة النفايات الصلبة في الوقت الحالي يبلغ 50%. افترضنا زيادة تدريجية في كفاءة عملية تسميد النفايات من إنتاجية 10 طن يومياً في 2014 إلى 200 طن يومياً عام 2025, وزيادة فعالية التدوير من 15% إلى 45% في العام 2025 مما يغطي العجز في ميزانية الإدارة 100%، بالإضافة إلى عائد بسيط من عمليتي بيع المفروزات وإنتاج السماد.Lattakia is now facing the need to renovate its Municipal Solid Waste Management system (MSWM), in accordance with the big increase in waste production, which is linked directly with the increasing number of city residents as a result of the crisis.In this study a System Dynamics (SD) computer model has been used to analyze the current municipal solid waste management system (MSWMS), and to develop a future optimized management strategy. Model is built after comparison between one scenario that takes into account the most influencing factors in waste generation, Population P and economic factor as indicator of standard of living, expressed by the Gross State Domestic Product GSDP and another scenario that does not take the retreating economic factor because of the crisis (predicted waste quantity of 400 k.ton/ year for 2025). This last scenario has been adopted as the most critical scenario. According to the results of Dynamic model, it is expected that the per capita generation rate of waste is reduced from 1.1 to 0.8 kg / per. day in 2025 with an increase in population to become 1.452 million people. The model reveals a deficit in the budget of MSWM at present about 50%. Assuming a gradual increase in the efficiency of compost production from 10 tons daily in 2014 to 200 tons per day in 2025, and increasing sorting efficiency from 15% to 45% in 2025, the model predicts a 100% cover of solid waste budget deficit in addition to a revenue from sorting and compost production